Perceived Challenges to Tribally Led Shellfish Toxin Testing in Southeast Alaska: Findings From Key Informant Interviews - Hugh B. Roland; Jacob Kohlhoff; Kari Lanphier; Sneha Hoysala; Esther G. Kennedy; John Harley; Christopher Whitehead; Matthew O. Gribble (GeoHealth, 2024)
Abstract Shellfish harvesting is central to coastal Alaska Native ways of life, and tribes in Southeast Alaska are committed to preserving sustainable and safe access to subsistence foods. However, consumption of non‐commercially harvested shellfish puts Alaska Native communities at elevated risk of exposure to shellfish toxins. To address a lack of state or federal toxin testing for subsistence and recreational harvesting, tribes across Southeast Alaska have formed their own toxin testing and ocean monitoring program. In this study, we interviewed environmental managers responsible for tribes' testing and others with shellfish toxin expertise to report on perceptions of barriers to tribally led testing in Southeast Alaska. Tribal staff identified 40 prospective key informants to interview, including all environmental managers responsible for shellfish toxin testing at subsistence sites in Southeast Alaska. All 40 individuals were invited to participate in an interview and 27 individuals were interviewed. The most frequently discussed barriers to shellfish toxin testing in Southeast Alaska relate to logistical and staffing difficulties associated with communities' remote locations, inconsistent and inadequate funding and funding structures that increase staff burdens, risk communication challenges related to conveying exposure risks while supporting subsistence harvesting, and implications of climate change‐related shifts in toxin exposures for risk perception and risk communication. Participants stressed the social origins of perceived barriers. Disinvestment may create and sustain barriers and be most severely felt in Native communities and remote places. Climate change impacts may interact with social and cultural factors to further complicate risk management.